Chemical ordering and electronic properties of lone pair chalcogenide semiconductors. (June 2019) - Sharma, Vineet; Sharda, Sunanda; Sharma, Neha; Katyal, S.C.; Sharma, Pankaj
Abstract: Chalcogenide lone pair semiconducting materials are important materials due to their prospective applications in thermoelectrics, phase change memories, topological insulators etc . Investigating these lone pair semiconductors for versatile applications, different electronic properties were studied by researchers world-wide. Analyses of these semiconducting materials in bulk and thin films for electronic properties like dark and photo-conductivity, photosensitivity, carrier concentration, carrier type, relaxation time and thermopower are the major constituents while accepting them for applications. This review stresses on the electronic properties of several binary, ternary and quaternary lone pair chalcogenide systems. The electronic properties are generally discussed on the basis of chemical ordering in system. A brief discussion on some theoretical background of conduction mechanism has also been incorporated for new researchers in this field. Potential applications of chalcogenide semiconducting materials have been outlined.